Unique polymer gel with magnetizable cobalt domains via photoinduced thiol-alkene hydrothiolation. (5th November 2020) - Kumar, Rajan; Mukherjee, Saikat; Lakshminarasimhan, Narayanan; Shunmugam, Raja
Graphical abstract: Highlights: In this article, we have developed a new strategy to synthesize an organo-magnetic 3D crosslinked polymer material showing ferromagnetism. Such material can be used to develop microelectronic devices, solid-state sensors, and a reaction catalyst. Even such system can be used for the mineralization of industrial toxicants. Moreover, oxides of cobalt (Cox Oy ) as the source for P-type semiconductors can play a significant role in the degradation of organic waste contaminants [40–41] . Such 3D crosslinked polymer model can be molded into magneto rheological materials with scope for application in medical science as well as in seismology [42] . Their utilization in the field of automobiles can be thought on the prospect of the future. Abstract: We introduce a new strategy to grow a photo clicked norbornene based well dispersed organo-magnetic three dimensional (3D) crosslinked polymer PNOR-MAG . The magnetic monomer NOR-Co provides the opportunity towards the growth of dispersed Cox OY magnetic units within PNOR-MAG . The material is investigated thoroughly using standard analytical techniques. The measured magnetic properties of PNOR-MAG reveal a change from diamagnetic to the ferromagnetic property upon annealing. Such water-resistive stable magnetic polymer has scope for its utilization as microelectronic devices related to data storage, act as solid-state sensors as well as a reaction catalyst. As magneto-rheological materials, such polymer can provide new scope for applications related to medical science as well as in seismology as a magnetic damper for resisting shock.